Naomi. The complete series [videorecording (DVD)] - DuVernay, Ava; Blankenship, Jill (Warner Bros. Entertainment Inc., 2022)
The DC drama follows a teen girl's journey from her small northwestern town to the heights of the Multiverse. When a supernatural event shakes her hometown to the core, Naomi sets out to uncover its origins, and what she discovers will challenge everything we believe about our heroes.